1991
DOI: 10.1084/jem.173.5.1039
|View full text |Cite
|
Sign up to set email alerts
|

Reentry of T cells to the adult thymus is restricted to activated T cells.

Abstract: SummaryTo seek information on the capacity of mature T cells to migrate to the thymus, mice were injected with Thy-l-marked populations enriched for resting T cells or T blast cells ; localization of the donor cells in the host thymus was assessed by staining cryostat sections of thymus and by FACS® analysis of cell suspensions . With injection of purified resting T cells, thymic homing was extremely limited, even with injection of large doses of cells. By contrast, in vivo generated T blast cells migrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
165
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(184 citation statements)
references
References 23 publications
18
165
0
1
Order By: Relevance
“…Mature B cells, as shown in this study, and APCs, as shown in other studies (7), do not efficiently circulate to the thymus, and therefore may not deliver Ag to newly developing T cells. It has been suggested that resting mature T cells recirculate into the thymus inefficiently when compared with activated T cells (21,22). In our experiments, we were able to detect a relatively high frequency of mature allogeneic T cells in the thymus.…”
Section: Discussionsupporting
confidence: 65%
“…Mature B cells, as shown in this study, and APCs, as shown in other studies (7), do not efficiently circulate to the thymus, and therefore may not deliver Ag to newly developing T cells. It has been suggested that resting mature T cells recirculate into the thymus inefficiently when compared with activated T cells (21,22). In our experiments, we were able to detect a relatively high frequency of mature allogeneic T cells in the thymus.…”
Section: Discussionsupporting
confidence: 65%
“…In the absence of CD5, an increased percentage of CD4 1 CD25 1 Foxp3 1 are generated at day 8 of culture, compared with WT FTOC (3.5470.3% versus 2.0270.32%; n 5 10, pr0.05), (Fig. 6A and B), demonstrating that nTreg are thymus derived and do not represent recirculating peripheral T cells homing to the thymus [54,55]. This increase in CD25 1 Foxp3 1 cells was also seen in the DP subpopulation (data not shown).…”
Section: Intracellular Tcr-mediated Signaling In Cd5 à/à Thymocytesmentioning
confidence: 95%
“…Interestingly, the vast majority of the small numbers of cells in the thymus (Ͻ 10 6 ) at this stage were also CD45.1 ϩ (Figure 3B), reflecting the previously described recirculation of activated mature donor T cells. 22 Finally, the FoxP3 ϩ T reg cells in the periphery of BM transplant recipients were also all CD45.1 ϩ and thus also derived from the mature donor T-cell inoculum within the graft ( Figure 3C). Having demonstrated that all T cells in the BM transplant recipients were peripherally expanded from the mature donor T-cell inoculum at this time, we next quantified donor FoxP3 Ϫ CD4 ϩ effector (T effector ) and T reg expansion in the periphery of WT and RelB Ϫ/Ϫ BMC recipients.…”
Section: Abrogation Of Gvhd Is Associated With Normal Donor T Reg Expmentioning
confidence: 99%